2020
DOI: 10.1007/s11011-020-00620-4
|View full text |Cite|
|
Sign up to set email alerts
|

Laterality and sex differences in the expression of brain-derived neurotrophic factor in developing rat hippocampus

Abstract: Brain-derived neurotrophic factor (BDNF), as a member of neurotrophin family, plays an important role in neurogenesis, neuronal survival and synaptic plasticity. BDNF is strongly expressed in the hippocampus, where has been associated with memory consolidation, learning, and cognition. In this study, Real-time PCR, immunohistochemistry, and stereology were used to evaluate the gender differences and left-right asymmetries in the expression of BDNF in the developing rat hippocampus during the neurogenesis-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…No difference was found in other regions of the right hippocampus (CA1, CA2, and CA3) or in the left hippocampus. No sex differences in BDNF expression are detectable at earlier points in development (P0 and P7) (Sardar et al, 2021). In humans BDNF was found to be expressed in higher levels in the female frontopolar PFC than in the male one.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 89%
See 1 more Smart Citation
“…No difference was found in other regions of the right hippocampus (CA1, CA2, and CA3) or in the left hippocampus. No sex differences in BDNF expression are detectable at earlier points in development (P0 and P7) (Sardar et al, 2021). In humans BDNF was found to be expressed in higher levels in the female frontopolar PFC than in the male one.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 89%
“…It is known to be differently expressed and involved in sexual dimorphic behaviors. So, the BDNF abundance in the hippocampus, the frontal cortex and the brain stem is higher in male mice over all regions (Szapacs et al, 2004;Sardar et al, 2021). Looking more closely at the hippocampus it was shown that the expression of BDNF in female Sprague-Dawley rats is higher in the CA3 region, lower in the DG and unchanged in the CA1 region compared to males (Franklin and Perrot-Sinal, 2006).…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 98%
“…BDNF plays an important role in synapse remodeling in the process of animal learning, memory, and cognition. Combined with its specific receptor tyrosine kinase receptor B (TrkB), it induces phosphorylation at specific sites of the TrkB receptor and transmits BDNF signals to the nucleus for neuroprotection ( 55 ). The immediate-early genes c-fos and c-jun belong to a class of proto-oncogenes which can be induced by second messengers to respond quickly to external stimuli such as neurotransmitters, hormones, and nerve impulses ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with its specific receptor tyrosine kinase receptor B (TrkB), it induces phosphorylation at specific sites of the TrkB receptor and transmits BDNF signals to the nucleus for neuroprotection. [45] The immediate-early genes c-fos and cjun belong to a class of proto-oncogenes which can be induced by second messengers to respond quickly to external stimuli such as neurotransmitters, hormones, and nerve impulses. These genes express their expression products as third messengers to participate in the regulation of the transduction of signals closely related to learning and memory in cells.…”
Section: Discussionmentioning
confidence: 99%